The bear went over the mountain - Wells, Rosemary; Raising Readers Collection (New York : Scholastic Press, 2006)
A bear goes over the mountain and all he could see was the other side.
On board pages.
NP
Keywords: Children's songs -- Texts; Bears -- Songs and music; Songs